Sociologie du loisir, sociologie du temps - Gilles Pronovost (Temporalités)
This text illustrates the interest of studying work schedules in order to empirically analyze the time actually dedicated to leisure. It takes off from a comparative analysis of original data from surveys carried out in the United States, France and Canada. Beyond the variability of the taxonomy employed, general trends clearly stand out : the growing amount of time given to leisure until the mid 1980s in the U.S.A. - ten years later in Canada and in France - then a levelling off, or even a decline, among the work force. At the center of the time dedicated to leisure, the amount given to sports remains relatively constant but the amount given to reading diminishes, a sign that cultural time is declining, and a recent increase in the amount spent in front of the TV screen appears. Analysis of variance suggests that it is how the work force relates to the non-working population, at different ages, that explains most of the variations observed in the three cases under study.